Design of a Greenhouse System for Vegetable Plants Based on the Internet of Things - Janne Deivy Ticoh; Junaedy Alexandrya Kaengke; Ridwan, Ridwan (Jurnal Sistem Cerdas, 2025)
This research aims to overcome the problem of lack of efficiency in Green House management in North Sulawesi. Where management is still done manually. The main problem in this research is the high cost of procuring a control system and farmers' lack of understanding regarding the Internet of Things (IoT). To solve this problem, an IoT based Green House control system was developed which integrates various sensors to monitor and control temperature, humidity and light intensity automatically. This system uses an ESP32 microcontroller and the Blynk application to facilitate remote monitoring. Trial results shows that this system is able to maintain optimal environmental conditions for plant growth, increase productivity, and reduce the risk of damage due to climate change. By implementing this system, it is hoped that farmers in North Sulawesi can optimize the use of resources and increase the quality and quantity of harvests make an important contribution to development of sustainable agriculture in the tropic